A Functional Variant in Ubiquitin Conjugating Enzyme E2 L3 Contributes to Hepatitis B Virus Infection and Maintains Covalently Closed Circular DNA Stability by Inducing Degradation of Apolipoprotein B mRNA Editing Enzyme Catalytic Subunit 3A. Issue 5 (15th March 2019) - Zhou, Li; Ren, Ji‐Hua; Cheng, Sheng‐Tao; Xu, Hong‐Mei; Chen, Wei‐Xian; Chen, Da‐Peng; Wong, Vincent Kam Wai; Law, Betty Yuen Kwan; Liu, Yi; Cai, Xue‐Fei; Tang, Hua; Yu, Hai‐Bo; et al.
Abstract : Hepatitis B virus (HBV) infection is a common infectious disease, in which nuclear covalently closed circular DNA (cccDNA) plays a key role in viral persistence, viral reactivation after treatment withdrawal, and drug resistance. A recent genome‐wide association study has identified that the ubiquitin conjugating enzyme E2 L3 ( UBE2L3 ) gene is associated with increased susceptibility to chronic HBV (CHB) infection in adults. However, the association between UBE2L3 and children with CHB and the underlying mechanism remain unclear. In this study, we performed two‐stage case–control studies including adults and independent children in the Chinese Han population. The rs59391722 allele in the promoter of the UBE2L3 gene was significantly associated with HBV infection in both adults and children, and it increased the promoter activity of UBE2L3 . Serum UBE2L3 protein levels were positively correlated with HBV viral load and hepatitis B e antigen (HBeAg) levels in children with CHB. In an HBV infection cell model, UBE2L3 knockdown significantly reduced total HBV RNAs, 3.5‐kb RNA, as well as cccDNA in HBV‐infected HepG2‐Na + /taurocholate cotransporting polypeptide cells and human primary hepatocytes. A mechanistic study found that UBE2L3 maintained cccDNA stability by inducing proteasome‐dependent degradation of apolipoprotein B mRNA editing enzyme catalytic subunit 3A, which is responsible for the degradation of HBV cccDNA. Moreover, interferon‐α (IFN‐α) treatment markedly decreased UBE2L3 expression, while UBE2L3 silencing reinforced the antiviral activity of IFN‐α on HBV RNAs, cccDNA, and DNA. rs59391722 in UBE2L3 was correlated with HBV DNA suppression and HBeAg loss in response to IFN‐α treatment of children with CHB. Conclusion: These findings highlight a host gene, UBE2L3, contributing to the susceptibility to persistent HBV infection; UBE2L3 may be involved in IFN‐mediated viral suppression and serve as a potential target in the prevention and treatment of HBV infection.